P419 Long-term outcome of ulcerative colitis in pediatric patients who achieved mucosal and histological healing: a real-life referral center experience. (21st January 2022) - Scarallo, L; Peruggia, E; Fioretti, L; Renzo, S; Paci, M; Naldini, S; Barp, J; Di Paola, M; Lionetti, P
Abstract: Background: Ulcerative colitis tend to present with a more extensive phenotype and a more aggressive behavior in pediatric populations when compared to adult ones. Treatment targets are shifting from symptom alleviation to more objective outcomes, such as the healing of the mucosa and the complete resolution of microscopic inflammation. However, data regarding real-life attainment of such outcomes and their prognostic implications are lacking. Methods: We performed a retrospective analysis on pediatric patients affected by UC who were followed up for at least, 12 month at a tertiary referral center. We included only patients who underwent endoscopic reassessment during clinical remission. Results: Eighty-four patients were included. At diagnosis, patients were divided with regard to the extent of disease as assessed by the Paris classification as follows:, 45 (53.6%) showed pancolitis E4, 2 (2.4%) left colitis E3, 22 (26.2%) proctosigmoiditis E2, and, 15 (17.8%) proctitis E1. Globally, 14 (16.7%) patients presented with an acute severe colitis (ASC) attack at diagnosis. The median age at diagnosis was, 13 years and, 7 months (IQR=94 months). Patients were followed for a median time of, 18 months (IQR:, 22 months). The second endoscopy was performed after a median time of, 27 months (IQR=32). At the second endoscopic re-evaluation, 64 (76.2%) patients out of the total had regression of disease; whereas, 20 (23.8%) patients out of the total had progression of disease. Twenty (23.8%) patients had a Mayo score of, 1, whereas, 36 (42.8%) patients had a Mayo score of, 0. Complete histological healing was achieved by, 17 (20.2%) patients. When observing recurrence-free survival, patients who achieved partial and complete MH showed a significantly higher recurrence-free survival (p<0.001 and p<0.001, respectively). Lastly, when considering only patients who achieved at least partial MH, the subgroup with complete HH showed lower recurrence rates compared to those with persistent microscopic inflammation (p=0.049) Conclusion: We reported the long-term outcomes of a selected group of pediatric patients with ulcerative colitis. Achievement of mucosal and histological healing appeared to protect against disease recurrence, with patients who resolved completely microscopic inflammation showing longer relapse-free survival rates.